Hind Swaraj and Ghandhi’s construction of Civilizational difference - Mishra, Prem Anand (Vidyapith (વિદ્યાપીઠ), 2015)
Is Gandhi's Hind Swaraj only a critique of modern civilization? If yes, then is there only one way to read this critique, as it has been generally read, in the form of hierarchical binary opposition of soul/body in which the former is valorized and latter is totally undermined? If not, then how can it be read in any other way? Given that Gandhi had more than a decade long political background when he wrote the text; might not Hind Swaraj and its critique of modern civilization be read as intervention in both nationalist and colonial discourses? In the backdrop of the above questions, this paper explores the relation between modern civilization and colonialism as the representational structure of Hind Swaraj and examines how Gandhi constructs a conceptual difference between Indian civilization and modern civilization to produce a new sense of national identity in which India is considered superior to their colonial masters on the spiritual ground. To support the argument above, at the methodological level, first the researcher builds an analytical framework consisting of discursive formation of the text Hind Swaraj to read its argument in the discursive context in which it was written and then presents textual analysis of the aforementioned theme.